Evaluation of Library Information System Quality Using the McCall Method - Rozi, Fachrul; Yenila, Firna; Ranni, Larissa Navia (Journal of Computer Scine and Information Technology, 2025)
The Inlis application at the West Sumatra Provincial Archives and Library Service is used to manage the process of borrowing and returning books carried out by each library member. With this library system, it can help librarians to find out the flow of books in and out and the delay in returns made by library members to determine the fines that must be paid by members. Based on this, the author will measure the quality of the Library Information System because in this system the level of system quality is not yet known, so as to identify the accuracy, completeness and quality of the software in the Inlis Application. The measurement method in this study is the McCall Method. The McCall Method is a software testing method that bridges the gap between users and developers that focuses on a number of software quality factors. Software quality can be interpreted as an effective process that is realized in the form of a product that can provide benefits and can be measured. The results of the study based on the McCall Method show that the quality of the Inlis Application is good with a percentage value of 72%, with the best indicator value, namely reliability with a result of 80% and the worst indicator value, namely integrity with a result of 44%.